The male gazed : on hunks, heartthrobs, and what pop culture taught me about (desiring) men - Betancourt, Manuel (Writer) (Catapult, 2023)
"Manuel Betancourt has long lustfully coveted masculinity--in part because he so lacked it. As a child in Bogotá, Colombia, he grew up with the social pressure to appear strong, manly, and, ultimately, straight. And yet in the films and television he avidly watched, Betancourt saw glimmers of different possibilities. From the stars of telenovelas and the princes of Disney films to pop sensation Ricky Martin and teen heartthrobs in shows like Saved By the Bell, he continually found himself asking: Do I want him or do I want to be him? The Male Gazed grapples with the thrall of masculinity, examining its frailty and its attendant anxieties even as it focuses on its erotic potential. Masculinity, Betancourt suggests, isn't suddenly ripe for deconstruction--or even outright destruction--amid so much talk about its inherent toxicity. Looking back over decades' worth of pop culture's attempts to codify and reframe what men can be, wear, do, and desire, this book establishes that to gaze at men is still a subversive act. Written in the spirit of Hanif Abdurraqib and Olivia Laing, The Male Gazed mingles personal anecdotes with cultural criticism to offer an exploration of intimacy, homoeroticism, and the danger of internalizing too many toxic ideas about masculinity as a gay man"--